Decreased Immunoreactivities of the Chloride Transporters, KCC2 and NKCC1, in the Lateral Superior Olive Neurons of Kanamycin-treated Rats - Myung-Whan Suh; Seung Cheol Ahn (Clinical and Experimental Otorhinolaryngology, 2012)
ObjectivesFrom our previous study about the weak expressions of potassium-chloride (KCC2) and sodium-potassium-2 chloride (NKCC1) co-transporters in the lateral superior olive (LSO) in circling mice, we hypothesized that partially damaged cochlea of circling mice might be a cause of the weak expressions of KCC2 or NKCC1. To test this possibility, we reproduced the altered expressions of KCC2 and NKCC1 in the LSO of rats, whose cochleae were partially destroyed with kanamycin.MethodsRat pups were treated with kanamycin from postnatal (P)3 to P8 (700 mg/kg, subcutaneous injection, twice a day) and sacrificed for immunohistochemical analysis, scanning electron microscope (SEM) and auditory brain stem response.ResultsThe SEM study revealed partially missing hair cells in P9 rats treated with kanamycin, and the hearing threshold was elevated to 63.8±2.5 dB SPL (4 ears) at P16. Both KCC2 and NKCC1 immunoreactivities were more prominent in control rats on P16. On 9 paired slices, the mean densities of NKCC1 immunoreactivities were 118.0±1.0 (control) and 112.2±1.2 (kanamycin treated), whereas those of KCC2 were 115.7±1.5 (control) and 112.0±0.8 (kanamycin treated).ConclusionWe concluded that weak expressions of KCC2 and NKCC1 in circling mice were due to partial destruction of cochleae.